Respuesta :
Answer:
the relations are:
Ln(a*b) = ln(a) + ln(b)
ln(a/b) = ln(a) - ln(b)
a*ln(b) = ln(b^a)
the relation used is:
1) exp(a)*exp(b) = exp(a+b)
and remember that exp(x) = y
means that ln(y) = x
then when we apply logaritm to both sides in the equation 1) we must have that:
ln( exp(a)*exp(b)) = ln(exp( a+b)) = a+ b
ln( exp(a)*exp(b)) = a + b
then
ln( exp(a)*exp(b)) = ln(exp(a)) + ln(exp(b)) = a + b
and you can use a similar thinking to prove the other ones, using that relationships and:
exp(a - b) = exp(a)/exp(b)
exp(a)^b = exp(a*b)